Structural, Electrical, And Optical Properties Of Indium Nitride Thin Films - Ganie, Umar Bashir (2018)
InN is the least studied material among III-V nitrides, due to the challenges associated with its low dissociation temperature and lack of suitable substrate. The discovery of a narrow band gap (0.7 eV) renewed the interest of researchers to carry out the detailed study of InN for optoelectronic applications. The commonly used growth techniques include molecular beam epitaxy and metalorganic chemical vapor deposition. Radio frequency (RF) sputtering is also commonly used for the growth of thin films and nanostructures, but it usually produces polycrystalline films with high carrier concentration and low electron mobility. However, the benefit of using RF sputtering are its low cost, easy to handle and produces InN films even at room temperature which is not possible with other mentioned techniques.